(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aimed to identify the impact of organizational conformity on enhancing the sustainability of institutional performance in the hotel sector in the Madinah region. This was achieved by analyzing its dimensions, namely workplace harmony and administrative transparency, and determining their contribution to supporting sustainable institutional performance from the employees’ perspective. The study employed a descriptive-analytical approach. The study population consisted of employees in licensed hotels in the Madinah region, from which a stratified random sample of 240 individuals was selected. Data were collected using a questionnaire developed based on previous literature, and its validity and reliability were verified using correlation coefficients and Cronbach’s alpha. The data were analyzed using several appropriate statistical methods. The study concluded that the level of organizational conformity among employees was high, and the level of enhancing institutional performance sustainability was also very high. Regression analysis revealed a statistically significant impact of organizational conformity on enhancing institutional performance sustainability, with administrative transparency proving to be the most influential dimension compared to workplace harmony. In light of the findings, the study recommended strengthening organizational alignment practices within hotels, supporting administrative transparency, and improving the work environment to contribute to achieving sustainable institutional performance.